Philosophy and Political Engagement Reflection in the Public Sphere - Fives, Allyn; Breen, Keith; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
Do philosophers have a responsibility to their society that is distinct from their responsibility to it as citizens? This edited volume explores both what type of contribution philosophy can make and what type of reasoning is appropriate when addressing public matters now. These questions are posed by leading international scholars working in the fields of moral and political philosophy. Each contribution also investigates the central issue of how to combine critical, rational analysis with a commitment to politically relevant public engagement. The contributions to this volume analyse issues raised in practical ethics, including abortion, embryology, and assisted suicide. They consider the role of ethical commitment in the philosophical analysis of contemporary political issues, and engage with matters of public policy such as poverty, the arts, meaningful work, as well as the evidence base for policy. They also examine the normative legitimacy of power, including the use of violence.
Keywords: Political science; Political theory; Public policy; Ethics; Political philosophy; Political Science and International Relations; Political Theory; Ethics; Political Philosophy; Public Policy; Electronic books